Policy interaction, expectations, and the liquidity trap - George W. Evans; Seppo Honkapohja (Federal Reserve Bank of Atlanta, 2003)
The authors consider inflation and government debt dynamics when monetary policy employs a global interest rate rule and private agents forecast using adaptive learning. Because of the zero lower bound on interest rates, active interest rate rules are known to imply the existence of a second, low inflation steady state, below the target inflation rate. Under adaptive learning dynamics the authors find the additional possibility of a liquidity trap, in which the economy slips below this low inflation steady state and is driven to an even lower inflation floor that is supported by a switch to an aggressive money supply rule. Fiscal policy alone cannot push the economy out of the liquidity trap. However, raising the threshold at which the money supply rule is employed can dislodge the economy from the liquidity trap and ensure a return to the target equilibrium.
Keywords: 330; Equilibrium (Economics); Monetary policy; Inflation (Finance); Macroeconomics; Liquidity (Economics)